Sauti ya Vijana (SYV; The Voice of Youth): Longitudinal Outcomes of an Individually Randomized Group Treatment Pilot Trial for Young People Living with HIV in Tanzania. - Dow, Dorothy E.; O'Donnell, Karen E.; Mkumba, Laura; Gallis, John A.; Turner, Elizabeth L.; Boshe, Judith; Shayo, Aisa M.; Cunningham, Coleen K.; Mmbaga, Blandina T. (AIDS & Behavior, 2022)
Sauti ya Vijana is a mental health and life skills intervention delivered by young adult group leaders for the improvement of HIV outcomes in young people living with HIV in Tanzania. This pilot randomized controlled trial estimated exploratory intervention effectiveness compared to standard of care. YPLWH (N = 105) were randomized to receive intervention or SOC. The mean age of participants was 18.1 years and 53% were female. Mean scores on mental health measures (Patient Health Questionnaire [PHQ-9], Strengths and Difficulties Questionnaire [SDQ], UCLA Trauma) were asymptomatic to mild in both study arms through 30-month follow-up with a non-significant fluctuation of 1–2 points. The mean self-reported adherence was higher in the intervention arm across all time points (but the confidence interval contained the null at all time points except 6 months). Risk ratio of virologic suppression (HIV RNA < 400 copies/mL) in the intervention arm compared to SOC was 1.15 [95% CI = 0.95, 1.39]) at 6-months, 1.17 [95% CI: 0.92, 1.48] at 12-months, and 0.99 [95% CI 0.76, 1.31] at 18-months. Though these findings were not powered for statistical significance, the trends in HIV outcomes suggest that SYV holds promise for improving antiretroviral therapy (ART) adherence and virologic suppression in YPLWH.